Hypomania Symptoms Across Psychiatric Disorders: Screening Use of the Hypomania Check-List 32 at Admission to an Outpatient Psychiatry Clinic - Camacho, Marta; Almeida, Sílvia; Moura, Ana Rita; Fernandes, Ana B.; Ribeiro, Gabriela; da Silva, Joaquim Alves; Barahona-Corrêa, J. Bernardo; Oliveira-Maia, Albino J. (Frontiers in Psychiatry, 2018)
Introduction: Hypomania symptoms are best described as a continuum, stretching beyond Bipolar Spectrum Disorders (BSD). Other nosological entities, such as major depressive disorders, schizoaffective disorders or borderline personality disorder, may also share symptoms with BSD, raising challenges for differential diagnosis. While the Hypomania Checklist-32 is one of the most widely used tools for screening hypomania, there is limited evidence describing its use in real-world outpatient psychiatric clinical setting. Methods: Here we tested the psychometric properties of a European Portuguese adaptation of the HCL-32, establishing its factor structure, reliability and construct validity. Furthermore, we analyzed differences in hypomanic symptoms among several clinical groups and in a non-clinical sample. Data was obtained retrospectively in an ecological setting from a clinical sample of an outpatient psychiatry and psychology clinic, comprising 463 Portuguese individuals, 326 of whom had a psychiatric diagnosis, namely BSD (n=66), major depressive disorder (n=116) or other psychiatric disorders (n=144). A separate non-clinical sample was also collected among healthy volunteers (n=62). A battery of self-report measures of affective symptoms was applied, and in a subset of patients, diagnosis was established using a structured diagnostic interview. Results: Psychometric properties of the HCL-32 were adequate, with good internal consistency (Cronbach’s α = 0.86) and test-retest stability (ICC= 0.86), and two subscores (‘active/elated’ and ‘risk-taking/irritable’) defined by Principal Component Analysis. Receiver Operating Characteristic curve analysis demonstrated that the test score discriminated moderately between patients with BSD and other clinical samples as well as healthy volunteers, with a cut-off score of 17 for the total score of the HCL-32 rendering the best combination of sensitivity and specificity. When compared to the HCL-32 total score, the risk-taking/irritable subscore seems to provide additional benefit in discriminating between different clinical groups, namely regarding specificity in the discrimination from patients with a diagnosis of major depressive disorder that was low for the full scale and the alternate subscale. Conclusions: HCL-32 can be used as a screening tool for BSD among adult patients presenting in an outpatient psychiatric clinical setting.